Overcoming racism in the twin spheres of conservation science and practice. Issue 1962 (10th November 2021) - Rudd, Lauren F.; Allred, Shorna; Bright Ross, Julius G.; Hare, Darragh; Nkomo, Merlyn Nomusa; Shanker, Kartik; Allen, Tanesha; Biggs, Duan; Dickman, Amy; Dunaway, Michael; Ghosh, Ritwick; González, Nicole Thompson; et al.
Abstract : It is time to acknowledge and overcome conservation's deep-seated systemic racism, which has historically marginalized Black, Indigenous and people of colour (BIPOC) communities and continues to do so. We describe how the mutually reinforcing 'twin spheres' of conservation science and conservation practice perpetuate this systemic racism. We trace how institutional structures in conservation science (e.g. degree programmes, support and advancement opportunities, course syllabuses) can systematically produce conservation graduates with partial and problematic conceptions of conservation's history and contemporary purposes. Many of these graduates go on to work in conservation practice, reproducing conservation's colonial history by contributing to programmes based on outmoded conservation models that disproportionately harm rural BIPOC communities and further restrict access and inclusion for BIPOC conservationists. We provide practical, actionable proposals for breaking vicious cycles of racism in the system of conservation we have with virtuous cycles of inclusion, equality, equity and participation in the system of conservation we want.